Marknadsundersökning om markägarens val av skogspartner - Johansson, Markus (SLU/School for Forest Management, 2011)
The driving forces from the forest owners point-of-view was studied on a market where several buyers attend to procure round-wood. It was concluded that forest owners prefer personal contacts to other means of communication, but that it is essential that the initial contact is a personal letter on paper. Furthermore, although price is always important, long standing relations is asked for. The buying companies need skillful experienced buyers that can provide more than just quick closures of deals.